化简求值:(﹣4x2+2x﹣8)﹣(x﹣1),其中x=.
举一反三
- 现化简,再求值:4x²-(x²+1)(2x-3)+(3x-2)(-3x-2)+(2x-1)(3-x)+(x-4)(x+1),其中x=-2
- 先化简,再求值:(x﹣1)2+x(x+2),其中x=.
- 求不定积分[img=112x35]17da6538063a9e4.png[/img]; ( ) A: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/ B: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4))/8 C: (x^4*log(x)^2)/4 - (x^4*(log(x) - 1/4)) D: (x^4*log(x)^2)/4 + (x^4*(log(x) - 1/4))/8
- 在x值处于-2~2、4~8时值为“真”,否则为“假”的表达式是______。 A: (2>x>-2)||(4>x>8) B: !(((x<-2)||(x>2))&&((x<=4)||(x>8))) C: (x<2)&&(x>=-2)&&(x>4)&&(x<8) D: (x>-2)&&(x>4)||(x<8)&&(x<2)
- 先化简,再求值:(x+2)(x-2)+(x+2)2,其中x=12.